Илья Ефимович Репин. 1844-1930 - Барагамян А. (Великие художники, 2010)
Экземпляры: Ф4 (20220207) / Инвентарный номер: 62532 / Цена: 168.00 / Сис.шифр: 85.14 / Авт.знак: Р 41 / ГРНТИ: 18.31.31 / ББК: 85.14